Impact of Macroeconomic Factors towards Price Index Performance in New York Stock Exchange Market - Yang, Zhiqiang; Li, Ke; Wang, Linxuan (INTI International University, 2024)
The NYSE is the world's biggest exchange market. Performance of the stock market has a big impact on how wealthy the economy is and how people live their daily lives. The stock price index, which serves as a benchmark for stock market performance, is a crucial tool for assessing each nation's economic situation. As a result, a significant amount of study has been done to determine how macroeconomic factors affect the performance of stock price indices. However, the literature does not support a consistent conclusion, but rather offers contradictory results. This study's objective is to dispel uncertainty in the literature by presenting fresh ideas that can improve descriptions of and understandings of stock price index performance. The aim of this research is to examine the New York Stock Exchange index for a span of four years that is between 2017 and 2021. Also, to examine stock price index performance and macroeconomics indicators. The NYSE Composite Index (NYA), which measures stock price index performance over the Nyse period 2017 to 2021, serves as the study's dependent variable (DV), and the GDP, rate of interest, inflation rate, and exchange rate serve as its independent variables (IVs). All of the companies listed and operating on the New York Stock Exchange (NYSE), as represented by NYA, are the study's target population. Secondary data were employed in this investigation. The DV data was acquired from NYSE websites, whilst the IVs were taken from reliable sources like the World Bank and International Money Fund. Regression analysis, descriptive statistics, and the reliability test were the only data analysis techniques used in this study.